How the Education Community Perceives Cyberbullying: a Comparison of Students, Teachers and Families - Pablo Bautista Alcaine; Eva Vicente Sánchez (Springer, 2020)
Abstract This study aims to find out how the groups that form the education community (students, teachers, families) differ in terms of the various characteristics surrounding the cyberbullying phenomenon. To do this, we conducted research using a selective correlational and cross-sectional design to analyze relationships and differences among variables: defining cyberbullying, typology, involved roles, possible causes and coping strategies in the different groups. The study recruited 116 participants as follows: 51% were year-6 Primary Education students; 29% were students' family members; 20% were school teachers. We collected data through an ad hoc questionnaire that a group of experts had previously validated. The results of the data analysis showed that significant differences appeared in terms of: how typologies were perceived; the importance of roles; coping strategies for cyberbullying.